Individual variation in migratory behavior in a subarctic partial migrant shorebird. (21st February 2020) - Méndez, Verónica; Alves, José A; Þórisson, Böðvar; Marca, Alina; Gunnarsson, Tómas G; Gill, Jennifer A
Abstract: Migratory behavior can differ markedly amongst individuals within populations or species. Understanding the factors influencing this variation is key to understanding how current environmental changes might influence migratory propensity and the distribution and abundance of migratory species across their range. Here, we investigate variation in migratory behavior of the partially migratory Eurasian oystercatcher ( Haematopus ostralegus ) population breeding in Iceland. We use the resightings of color-ringed adults and stable isotopes to determine whether individuals migrate or remain in Iceland during winter and test whether individual migratory strategies vary in relation to sex, body size, and breeding location. We also explore individual consistency in migratory strategy and test whether assortative mating with respect to strategy occurs in this population. The proportion of migrants and residents varied greatly across breeding locations but not with respect to sex or body size. Individuals were consistent in migratory strategy between years and there was no evidence of assortative mating by migratory strategy. We use these findings to explore factors underlying the evolution and maintenance of partial migration at high latitudes. Abstract : The majority of species that breed at high latitudes are migratory. However, in Iceland, not all breeding oystercatchers leave in autumn. By identifying individuals that stay in Iceland or migrate to Europe, we show that the frequency of residents and migrants varies across Iceland, and individuals choose their mates independent of their migratory status. We also found that individuals are consistently either migrant or resident, suggesting that individual migratory behavior is determined in early life.